Village banking and the millennium development goals: an innovative way to fighting poverty - Scofield, Rupert (Revista Española de Desarrollo y Cooperación, 2023)
Improved income as a result of the Village Banking microfinance model means progress in all eight Millennium Development Goals – not just in the eradication of poverty. As clients generate more income from new or expanded businesses, they also tend to make improvements in areas related to education, health and their overall standard of living.